2015
DOI: 10.5455/medarh.2015.69.177-180
|View full text |Cite
|
Sign up to set email alerts
|

Representation of Streptococcus Pneumoniae in Outpatient Population of Sarajevo Canton

Abstract: Introduction:Streptococcus pneumoniae in asymptomatic manner colonize the mucous membranes of the nasopharynx of children and adults, but can cause serious illness in the media which are naturally sterile. In 5-40% of healthy population this bacteria colonize the nasopharyngeal mucosa thanks to the surface adhesin protein, which allow the bacteria to attach to the epithelial cells. The normal nasopharyngeal microflora retains pneumococcus in a small number and does not allow it to express its pathogenic potent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 9 publications
(9 reference statements)
0
1
0
Order By: Relevance
“…About 50% of the colonized patients were in the preschool age. Previous studies reported that colonization by S. pneumoniae occurs usually at a young age with a peak in children of preschool age [11,19,20].…”
Section: Discussionmentioning
confidence: 99%
“…About 50% of the colonized patients were in the preschool age. Previous studies reported that colonization by S. pneumoniae occurs usually at a young age with a peak in children of preschool age [11,19,20].…”
Section: Discussionmentioning
confidence: 99%